Impact of a controlling coaching style on athletes’ fear of failure: Chain mediating effects of basic psychological needs and sport commitment - Hu, Qing; Li, Peng; Jiang, Bo; Liu, Bo (Frontiers in Psychology, 2023)
This study investigated the effect of a controlling coaching style on athletes’ fear of failure, as well as the chain mediating effects of basic psychological needs and sport commitment. A questionnaire survey of 252 active athletes was conducted using scales for fear of failure, controlling coaching style, sport commitment, and basic psychological needs. The results indicated that a controlling coaching style was negatively correlated with basic psychological needs and indirectly affected athletes’ fear of failure via basic psychological needs and constrained commitment. The chain mediating effect of basic psychological needs on enthusiastic commitment was not significant, but it was for constrained commitment. In conclusion, the impact of a controlling coaching style on athletes’ fear of failure via basic psychological needs is manifested through the strengthening of constrained commitment rather than the weakening of enthusiastic commitment.These findings contribute to a deeper understanding of why and how a controlling coaching style influences athletes' fear of failure. Coaches should seek more scientific and effective ways to instruct their athletes.